Early Victimization as Social Factor of Sexual Delinquency - Kuzmanović, Marija (Zbornik Instituta za kriminološka i sociološka istraživanja, 2013)
In this paper, the results of empirical research on the influence of early victimisation in the family and wider community on children and adolescents during the period of maturisation, and its reflections on their behaviour as mature persons, are presented. The starting point of research was the presumption that early victimisation, in the first place, manifested through physical, psychological (emotional) and sexual violence, later infects criminal behaviour in mature age. The exploration of early victimisation and its results, as represented in this work, includes the period of research between December 2007 and May 2008, on a sample of 296 examinees, divided into three groups. The experimental and the first control group were convicted persons who are serving a prison sentence. Inmates from the first experimental group were sexual perpetrators. Examinees from the first control group were inmates serving sentences for various crimes, but not sexual crimes. The third group of examinees, the second control group, was selected from the general male population. As an instrument for data collection was developed a structurated query, combined of open and questions with given answers. In the research, the World Health Organisation definition was accepted because of its comprehensive approach to sexual crimes. Results acquired in this research have shown that a high percentage of examinees from the experimental and first control group have been physically and psychologically victimised during adolescence. Indications of violent sexual behaviour against examinees haven’t been recorded. Also, there is a high percentage of accordance of the presented results with the results of other research on the question of exposure of sexually violent perpetrators to physical, psychological (emotional) and sexual violence.